Rights and Obligations for Floor and Flats Ownesrs in the Palestinian law "Comparative Study" - Faris Marwan Nasuh Bazian (My University, 2015)
This research discusses apartments and floors owners rights and commitments in the Palestinian law and the increasing number of multi floors buildings and the rising number of people living in > with the increase interior emigration from country side to cities , an urgent need to study laws which organizes apartment’s owners’ righties of multi floor buildings becomes essential . And for this target, it was the key point of this research, the Palestinian law (no1) , 1996 and its executive list , (no 2) for the year 1997 since it is the law which organics the building’s rights and commitments . The research is based on the article study in reading Palestinian law articles (no1) for the year 1996 for having the best analysis of this law and introducing the righties which the law gave to the buildings’ owners’ for the which parts of the structure. It becomes apparent in this sturdy the definition of flats’ owner ship system and how to apply it . the result is that the Palestinian lawgiver didn’t offer any sufficient guaranties for buyers . on the contrary of the Jordanian legislation . moreover , this study differentiates between flats ownership system and Height and marasmus system considering it one of the most suitable systems studying multi floors buildings conditions . this type of ownership has a dual condition, it decided the rights’ and commitments’ of multi apartments buildings into two types their tights and other obligations’ in using their properties and their legal and financial behaviors in the frames . That the Palestinian law for apartments and floors (no1) for the year 1996 showed . also its executives list (no2) for the year 1997. In addition , it showed the rights and obligations’ of floors and apartments owners on shared parts in setting sip, it discussed the way of using them and the legal and financial behavior depending on the basics which the Palestinian law for floors and apartments found {(no1) for the year 1996 and its executive list (no2) for the year 1997 , including also comparative study with the related Jordanian legislation , particularly , the Jordanian floors and apartments law ( no25) for the year 1968 and its corrections . By the end of this study , I recommended the necessity of correcting some of the articles of this law. At the same time its seams important to me to add new created ones in order to have the best legitacy which gives the best expected results to provid a high protections for floors and apartments owners.

تناولت هذه الرسالة موضوع حقوق وإلتزامات مالكي الطبقات والشقق في القانون الفلسطيني, فمع إزدياد التطور العمراني الذي تشهده الأراضي الفلسطينية , وإزدياد أعداد الأبنية ذات الطبقات المتعددة, وتزايد أعداد ساكنيها, ومع تزايد هجرة السكان الداخلية من الأرياف إلى المدن, صارت الحاجة ملحة لدراسة القوانين التي تنظم حقوق مالكي هذه الشقق والطبقات في الأبنية ذات الطبقات المتعددة . ولهذا الغرض , كان صلب دراستي في هذه الرسالة, القانون الفلسطيني رقم 1 لسنة 1996 ولائحته التنفيذية رقم 2 لسنة 1997, كونه القانون الذي ينظم حقوق وواجبات مالكي الوحدات العقارية في الأبنية . وإستخدمت في هذه الرسالة, أسلوب المنهج النظري, وذلك في إستقراء نصوص القانون الفلسطيني رقم 1 لسنة 1996, من أجل الوصول إلى أفضل قراءه لهذا القانون, ومعرفة الحقوق التي خولها ذلك القانون لمالك الطبقة أو الشقة على كامل أجزاء البناء. وبينت من خلال هذه الرسالة ماهية نظام ملكية الطبقات والشقق وشروط تطبيقه, وخلصت بأن المشرع الفلسطيني لم يوفر أي من الضمانات الكافية لمشتري الشقق على المخططات أو مشتريها على التقسيط, بعكس الحال في التشريع الأردني, كما وتمت التفرقة ما بين نظام ملكية الطبقات والشقق ونظام العلو والسفل, بأعتباره أقرب الأنظمة التي تحكم حالة الأبنية متعددة الشقق والطبقات. ولكون هذا النوع من الملكية ذا طبيعة مزدوجة, قسمت الحقوق والإلتزامات الملقاة على عاتق ملاك الطبقات والشقق إلى قسمين, حقوق مخولة لهم وإلتزامات ملقاة على عاتقهم في إستعمال وإستغلال والتصرف المادي أو القانوني في ملكهم المفرز, وذلك وفق الأطر التي بينها قانون الطبقات والشقق الفلسطيني رقم 1 لسنة 1996, وكذلك لائحته التنفيذية رقم 2 لسنة 1997. كذلك بينت الحقوق والإلتزامات الخاصة بملاك الطبقات والشقق على الأجزاء المشتركة في البناء, من كيفية إستعمالها وإستغلالها والتصرف المادي أو القانوني بها, وذلك وفق الأسس التي أوجدها قانون الطبقات والشقق الفلسطيني رقم 1 لسنة 1996 ولائحته التنفيذية رقم 2 لسنة 1997, وذلك كله في دراسة مقارنة مع التشريعات الأردنية الخاصة بهذا الشأن , وأهما قانون الطوابق والشقق الأردني رقم 25 لسنة 1968 وتعديلاته. وفي نهاية هذه الرسالة, أوصيت بضرورة تعديل بعض نصوص هذا القانون , وبذات الوقت أوصيت بإضافة نصوص مستحدثة له , من أجل الوصول إلى أفضل تشريع يحقق الغاية المنشودة منه , وذلك لتوفير أكبر حماية لمالكي الطبقات والشقق .
حقوق وإلتزامات مالكي الطبقات والشقق في القانون الفلسطيني/دراسة مقارنه